Study on the Bearing Capacity of High-Cap Inclined Pile Foundations - Guodong Shao; Juan Liu; Tonglei Wang; Yuping Liu (Advances in Civil Engineering)
To analyze the bearing capacity of high-cap inclined pile foundations based on foundation design in practical engineering, finite element models of single cap foundations and multi-cap foundations are established. The influence of the inclination direction and angle of the inclined pile on the lateral displacement of the foundation and internal force of the pile body is investigated. The influence of uneven settlement on inclined pile foundations is examined by weakening the soil strength. This paper suggests that the lateral bearing capacity of a negatively inclined pile is better than that of a positively inclined pile. When the inclination angle of a negatively inclined pile changes within a certain range, it can significantly affect the lateral displacement of the pile body. Under uneven settlement, the change in the internal force of the inclined pile is larger than that of the vertical pile, the horizontal displacement difference of each bearing platform is small, and the vertical displacement is quite different.